2020
DOI: 10.3168/jds.2020-19001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of combinations of nisin, lauric arginate, and ε-polylysine to control Listeria monocytogenes in queso fresco

Abstract: Listeria monocytogenes contamination is of great concern in queso fresco (QF), and listeriosis outbreaks linked to consumption of QF continue to happen. Hurdle approaches such as combining antimicrobials provide an alternative to improve QF safety. In this work, the efficacy of antimicrobial combinations of nisin (NIS), lauric arginate (LAE), and ε-polylysine (EPL) to inhibit L. monocytogenes growth in QF was evaluated. First, antimicrobials were screened for potential synergy in vitro. Later, antimicrobial tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…L. monocytogenes counts in control cheeses reached approximately 5.5 Log CFU/g by day 14 of storage at 4 °C, an increase of about 2 Log CFU from the initial inoculum. Similar to our previous studies ( Feng et al, 2019 ; Ibarra-Sánchez et al, 2021 ; Ibarra-Sánchez et al, 2018 ; Martínez-Ramos et al, 2020 ), a discreet reduction in the pathogen counts was observed in cheeses added with free nisin compared to control cheeses. The limited antilisterial efficacy of nisin in Queso Fresco is the result of nisin's instability at near-neutral pH, and interactions with milk fat, caseins, and cations ( Ibarra-Sánchez et al, 2020 ).…”
Section: Resultssupporting
confidence: 89%
“…L. monocytogenes counts in control cheeses reached approximately 5.5 Log CFU/g by day 14 of storage at 4 °C, an increase of about 2 Log CFU from the initial inoculum. Similar to our previous studies ( Feng et al, 2019 ; Ibarra-Sánchez et al, 2021 ; Ibarra-Sánchez et al, 2018 ; Martínez-Ramos et al, 2020 ), a discreet reduction in the pathogen counts was observed in cheeses added with free nisin compared to control cheeses. The limited antilisterial efficacy of nisin in Queso Fresco is the result of nisin's instability at near-neutral pH, and interactions with milk fat, caseins, and cations ( Ibarra-Sánchez et al, 2020 ).…”
Section: Resultssupporting
confidence: 89%
“…The MIC of ε-PL in the co-cultured strain was 1.0 mg/mL. ε-PL has been shown to have antimicrobial effects against Gram-positive and Gram-negative bacteria, yeast, and fungi [ 31 , 32 , 33 ]. Some reports suggest that the optimal MIC levels are 0.1 and 0.05 mg/mL for S .…”
Section: Resultsmentioning
confidence: 99%
“…typhimurium , respectively [ 32 ]. In addition, L. monocytogenes and E. coli showed MIC values at 125 and 19.53 μg/mL, respectively [ 31 , 33 ]. These differences can be attributed to the use of the food grade (low purity) and the tested strain.…”
Section: Resultsmentioning
confidence: 99%
“…32 EPL has also been shown to be listeriastatic when combined with LAE, over a 28 d shelf life, but consumers were able to differentiate the treated product. 33 Glycolipids, a biosurfactant, have been evaluated as a way of addressing L. monocytogenes contamination at different steps within the QF production. 34 This treatment was effective at reducing biofilms on polysterene and stainless steel.…”
Section: ■ Preservatives: Phages and Endolysinsmentioning
confidence: 99%